Environmental governance for sustainable development East Asian perspectives - Mori, Akihisa, 1970- (United Nations University Press, 2013)
"In order to advance global sustainable development it is indispensable to change the course and mode of conventional economic growth in the East Asian region, which has enjoyed rapid economic growth but faces environmental challenges. This volume gives attention to the evolution of multi-level environmental governance in the East Asian region, including both Northeast and Southeast Asia. It examines how effective emerging environmental governance and policy has been and addresses the underlying causes of local, national, regional and global environmental challenges. Topical chapters include democratization and its effect on decision-making processes, international environmental aid, economic analysis of carbon reduction policy, regional and global environmental regimes and subsequent new financial mechanisms, and hybrid systems of environmental governance that emphasize the role of the private sector and civil society in contributing to environmental governance. This volume gives special attention to the regional economic and environmental regimes. It examines the advantages, challenges and solutions in addressing local, national, regional and global environmental challenges, and in changing the course of economic growth"--